2017
DOI: 10.2147/ceg.s132004
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound-guided biliary drainage versus percutaneous transhepatic biliary drainage after failed endoscopic retrograde cholangiopancreatography: a meta-analysis

Abstract: The failure rate of endoscopic retrograde cholangiopancreatography for biliary cannulation is approximately 6%–7% in cases of obstructive jaundice. Percutaneous transhepatic biliary drainage (PTBD) is the procedure of choice in such cases. Endoscopic ultrasound-guided biliary drainage (EGBD) is a novel technique that allows biliary drainage by echoendoscopy and fluoroscopy using a stent from the biliary tree to the gastrointestinal tract. Information in PubMed, Scopus, clinicaltrials.gov and Cochrane review we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 43 publications
0
31
0
1
Order By: Relevance
“… 6 Randomised comparative trials and meta-analyses of EUS-BD and PTBD have demonstrated that while clinical and technical success show comparable efficacy, there are lower rates of reintervention and fewer post procedure adverse events (AEs) with EUS-BD. 5 7 8 For instance, one randomised trial conducted by highly experienced endoscopists showed that compared with PTBD, EUS-BD demonstrated fewer procedure-related AEs (31% vs 9%) in addition to lower frequencies of unscheduled reintervention (0.93 vs 0.34). 9 …”
Section: Introductionmentioning
confidence: 99%
“… 6 Randomised comparative trials and meta-analyses of EUS-BD and PTBD have demonstrated that while clinical and technical success show comparable efficacy, there are lower rates of reintervention and fewer post procedure adverse events (AEs) with EUS-BD. 5 7 8 For instance, one randomised trial conducted by highly experienced endoscopists showed that compared with PTBD, EUS-BD demonstrated fewer procedure-related AEs (31% vs 9%) in addition to lower frequencies of unscheduled reintervention (0.93 vs 0.34). 9 …”
Section: Introductionmentioning
confidence: 99%
“…In cases of bile duct obstruction, the treatment of choice is bile duct stenting via endoscopic retrograde cholangiopancreatography (ERCP). If the ampulla of Vater or the bile duct cannot be accessed, percutaneous transhepatic biliary drainage (PTBD) is performed, but currently, endoscopic ultrasound-guided biliary drainage (EUSBD) is also used in a number of centers [2022]. As demonstrated by Imai et al , in cases where bile duct stenting via ERCP is not possible due to lack of access, while EUSBD would be difficult due to factors such as duodenal stenosis, bile duct wall thickening, interposing blood vessels, or non-dilated intrahepatic bile ducts, the use of EUSGBD instead of PTBD may be considered (as the patient might want to avoid having a percutaneous catheter placed), provided that the cystic duct is unobstructed [23].…”
Section: Discussionmentioning
confidence: 99%
“…PTC ( Figure 1D) has been challenged by endoscopic and lately EUS approaches and the frequency of PTC has gradually decreased (25,26). The insertion of a wire for rendezvous, a plastic drain for internal and/or external (Yamakawa-/ Münchner-drainage) as well as a metal stent are well established, but there is a higher risk for complications and impact on quality of life compared to EUS approaches (27). Although these percutaneous interventions represent an appreciated salvage procedure, if local EUS expertise is available, PTC should be considered only after both ERCP and EUS-BD attempts have failed or are not suitable (27).…”
Section: Percutaneous Transhepatic Cholangiography (Ptc)mentioning
confidence: 99%